The effect of endodontic materials on the optical density of dyes used in marginal leakage studies - Kubo, Claudio Hideki [UNESP]; Valera, Marcia Carneiro [UNESP]; Gomes, Ana Paula Martins [UNESP]; Mancini, Maria Nadir Gasparoto [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP] (FapUNIFESP (SciELO), 2008)
The aim of this study was to determine the effect of the exposure of different endodontic materials to different dye solutions by evaluating the optical density of the dye solutions. Seventy-five plastic tubes were filled with one of the following materials: AH Plus, Sealapex, Portland cement, MTA (Angelus and Pro Root) and fifteen control plastic tubes were not. Each specimen of material and control was immersed in a container with 1 ml of each dye solution. A 0.1 ml-dye solution aliquote was removed before immersion and after 12, 24, 48 and 72 hours of each specimen immersion to record its optical density (OD) in a spectrophotometer. Statistical analysis was performed with ANOVA and Tukey tests (5%). No significant difference was found among any of the solution OD values for AH Plus cement. Portland cement promoted different OD values after 12 hours of immersion. MTA-Angelus cement presented different OD values only for 2% rhodamine B and the MTA-Pro Root cement presented different OD values in all 2% rhodamine B samples. Sealapex cement promoted a reduction in the India Ink OD values. Dye evaluation through OD seems to be an interesting method to select the best dye solution to use in a given marginal leakage study.
Keywords: Dental leakage; Methods; Methylene blue; Spectrophotometry; coloring agent; methylene blue; root canal filling material; tooth cement; analysis of variance; chemistry; materials testing; methodology; pH; spectrophotometry; time; tooth disease; Analysis of Variance; Coloring Agents; Dental Cements; Dental Leakage; Hydrogen-Ion Concentration; Materials Testing; Methylene Blue; Root Canal Filling Materials; Time Factors